«ШӘРИЯР» ДӘСТАНЫН ОҚЫТЫЎДА ИНТЕРАКТИВ МЕТОДЛАРДАН ПАЙДАЛАНЫЎДЫҢ НӘТИЙЖЕЛИЛИГИ - Алламбергенов, Е.К. (SCIENCE and SOCIETY, 2020)
The article discusses the effectiveness of the use of innovative technologies, including interactive methods in the teaching of literature lessons. The researcher proves with convincing examples that such methods as "corners", "Sinkvein", "IREC" are effective methods of teaching the epic "Shariyar" in an interactive way.
Keywords: «Shariyare» epos; innovation technology; interactive method; «corners» method; cinquuain method; IREC technology; innovative technology and results